Model Of The Influence Of Diarrhea In Purbalingga District Central Of Java - tjipto rini; Kuat Prabowo; Kusrini Wulandari (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2022)
One of the causes of diarrhea is the behavior of the community and as an indicator of Clean and Healthy Living Behavior in household arrangements. In fact, all of this cannot be separated from the participation and commitment of the local Public Health Center's staff. This study aims to determine the effect of organizational commitment on community culture, sanitation hygiene and the incidence of diarrhea in the community. The sample used in this study is the people who live in the working area of five Public Health Centers in Purbalingga district. The research data were obtained from the results of distributing questionnaires which were then analyzed using Partial Least Square analysis techniques. Based on the results of the analysis in this study, it was concluded that: 1) the organizational commitment of the puskesmas officers had an effect on the creation of a good community culture, 2) the organizational commitment of the Public Health Centers officers had an effect on the sanitation hygiene formed in the community around the Public Health Centers, 3) the organizational commitment of the Public Health Centers officers. also affects the incidence of diarrhea in the community, 4) good community culture will support the creation of good sanitation hygiene, 5) good community culture can support the low incidence of diarrhea in the community and 6) sanitation hygiene affects the incidence of community .